MELACAK GELAR KARAWITAN PUJANGGA LARAS TAHUN 2001-2009 (Upaya Pendokumentasian Ragam Gending) - Suraji Suraji (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2017)
AbstractThis research entitled Tracing the Performance of Karawitan Pujangga Laras from 2001 - 2009 is concerned with both textual and contextual issues. One issue that continues to appear up to the present time is that whenever the same gending is played by different musicians, the result will also be different. In the Surakarta karaton, the existence of Javanese karawitan in Surakarta style has undergone significant developments from one era to another. The increasing number of gending klenèngan in the repertoire has led to a variety of different treatment or interpretational style (garap). Treatment that had not previously been used has been reinterpreted and subsequently influenced the development of interpretational style in the present day.This research aims to document the repertoire of gending klenèngan performed by the karawitan group Pujangga Laras. In the performance of these gending, the Pujangga Laras group is not restricted to classical gending from the karaton. Instead, musicians are given the opportunity to perform other works, including new works composed by musicians or pesindhèn (female vocalists) who are active in the group, or gending composed by Ki Nartosabda. The results of this research show that during an 8 year period, Pujangga Laras performed over 400 gending in various forms. Although there is frequent repetition of certain gending, the outcome or result is always different. These differences are caused by a number of factors, including the venue, the musicians’ ability to interpret the gending, and so on. Keywords: Pujangga Laras, Repertoire, Gendhing. AbstrakPenelitian Melacak Gelar Karawitan Pujangga Laras Tahun 2001 - 2009 menyangkut persoalan tekstual dan kontekstual. Permasalahan yang muncul hingga kini adalah setiap gending yang sama bila disajikan oleh penggarap yang berbeda hasilnya juga berbeda. Di karaton Surakarta dari masa ke masa, keberadaan karawitan Jawa gaya Surakarta secara bertahap telah mengalami perkembangngan yang cukup signifikan. Makin banyaknya repertoar gending-gending klenèngan berdampak terhadap keragaman garap. Garap yang belum muncul sebelumnya, kemudian ditafsir kembali dan selanjutnya mempengaruhi perkembangan garap saat ini.Penelitian ini berupaya untuk mendokumentasi repertoar gending-gending klenèngan yang disajikan oleh kelompok karawitan Pujangga Laras. Dalam menyajikan gending-gending, kelompok karawitan Pujangga Laras tidak dibatasi pada gending klasik karaton, melainkan para pengrawit diberi kesempatan untuk menyajikan karya lain, baik karya baru hasil susunan pengrawit dan atau pesindhèn yang aktif dalam pergelaran tersebut, atau gending karya Ki Nartosabda. Hasil penelitian ini, dalam kurun waktu 8 tahun, ditemukan bahwa karawitan Pujangga laras telah menyajikan lebih dari 400 gending dalam berbagai bentuk.Kendatipun setiap pergelaran sering terjadi pengulangan gending yang sama, akan tetapi hasilnya tetap beerbeda. Perbedaan ini disebabkan oleh berbagai faktor, antara lain: tempat penyelenggaraan, kemampuan pengrawit dalam tafsir garap dan lain lain. Kata Kunci: Pujangga Laras, Repertoar, Gendhing.